Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

If [tex]x=\left(a+\sqrt{a^2+b^3}\right)^{1/3}+\left(a-\sqrt{a^2+b^3}\right)^{1/3}[/tex], then prove that [tex]x^3+3bx=2a[/tex].

Hint: Let [tex]m=\left(a+\sqrt{a^2+b}\right)^{1/3}[/tex] and [tex]n=\left(a-\sqrt{a^2+b}\right)^{1/3}[/tex]. Then, [tex]m+n=2a[/tex] and [tex](mn)^{1/3}=-b[/tex].


Sagot :

Certainly! Let's prove that [tex]\( x^3 + 3bx = 2a \)[/tex] given [tex]\( x = \left(a + \sqrt{a^2 + b^3}\right)^{1/3} + \left(a - \sqrt{a^2 + b^3}\right)^{1/3} \)[/tex].

### Step-by-Step Solution:

1. Define the Variables:
Let [tex]\( m = \left(a + \sqrt{a^2 + b^3}\right)^{1/3} \)[/tex] and [tex]\( n = \left(a - \sqrt{a^2 + b^3}\right)^{1/3} \)[/tex].

2. Express [tex]\( x \)[/tex] in Terms of [tex]\( m \)[/tex] and [tex]\( n \)[/tex]:
Therefore, we have [tex]\( x = m + n \)[/tex].

3. Cube [tex]\( x \)[/tex]:
We are asked to find [tex]\( x^3 \)[/tex]. Using the binomial theorem for [tex]\( (m+n)^3 \)[/tex], we get:
[tex]\[ x^3 = (m + n)^3 = m^3 + n^3 + 3mn(m + n) \][/tex]

4. Compute [tex]\( m^3 \)[/tex] and [tex]\( n^3 \)[/tex]:
From the definitions, [tex]\( m^3 = a + \sqrt{a^2 + b^3} \)[/tex] and [tex]\( n^3 = a - \sqrt{a^2 + b^3} \)[/tex].

5. Sum [tex]\( m^3 \)[/tex] and [tex]\( n^3 \)[/tex]:
[tex]\[ m^3 + n^3 = (a + \sqrt{a^2 + b^3}) + (a - \sqrt{a^2 + b^3}) = 2a \][/tex]

6. Determine [tex]\( mn \)[/tex]:
To compute [tex]\( mn \)[/tex]:
[tex]\[ mn = \left( \left(a + \sqrt{a^2 + b^3}\right)^{1/3} \right) \left( \left(a - \sqrt{a^2 + b^3}\right)^{1/3} \right) \][/tex]

Notice:
[tex]\[ mn = \left( (a + \sqrt{a^2 + b^3})(a - \sqrt{a^2 + b^3}) \right)^{1/3} = \left( a^2 - (\sqrt{a^2 + b^3})^2 \right)^{1/3} = \left( a^2 - (a^2 + b^3) \right)^{1/3} = (-b^3)^{1/3} = -b \][/tex]

7. Substitute Values in the Expansion:
Recall the expansion [tex]\( x^3 = m^3 + n^3 + 3mn(m + n) \)[/tex]:

Using [tex]\( m+n = x \)[/tex], [tex]\( m^3 + n^3 = 2a \)[/tex], and [tex]\( mn = -b \)[/tex], it follows that:
[tex]\[ x^3 = 2a + 3(-b)x \][/tex]

8. Result:
Rearrange the terms:
[tex]\[ x^3 + 3bx = 2a \][/tex]

Thus, we have proved that:
[tex]\[ x^3 + 3bx = 2a \][/tex]
as required.

Answer:

Certainly! Let's prove that

3

+

3

=

2

x

3

+3bx=2a given

=

(

+

2

+

3

)

1

/

3

+

(

2

+

3

)

1

/

3

x=(a+

a

2

+b

3

)

1/3

+(a−

a

2

+b

3

)

1/3

.

### Step-by-Step Solution:

1. Define the Variables:

Let

=

(

+

2

+

3

)

1

/

3

m=(a+

a

2

+b

3

)

1/3

and

=

(

2

+

3

)

1

/

3

n=(a−

a

2

+b

3

)

1/3

.

2. Express

x in Terms of

m and

n :

Therefore, we have

=

+

x=m+n .

3. Cube

x :

We are asked to find

3

x

3

. Using the binomial theorem for

(

+

)

3

(m+n)

3

, we get:

3

=

(

+

)

3

=

3

+

3

+

3

(

+

)

x

3

=(m+n)

3

=m

3

+n

3

+3mn(m+n)

4. Compute

3

m

3

and

3

n

3

:

From the definitions,

3

=

+

2

+

3

m

3

=a+

a

2

+b

3

and

3

=

2

+

3

n

3

=a−

a

2

+b

3

.

5. Sum

3

m

3

and

3

n

3

:

3

+

3

=

(

+

2

+

3

)

+

(

2

+

3

)

=

2

m

3

+n

3

=(a+

a

2

+b

3

)+(a−

a

2

+b

3

)=2a

6. Determine

mn :

To compute

mn :

=

(

(

+

2

+

3

)

1

/

3

)

(

(

2

+

3

)

1

/

3

)

mn=((a+

a

2

+b

3

)

1/3

)((a−

a

2

+b

3

)

1/3

)

Notice:

=

(

(

+

2

+

3

)

(

2

+

3

)

)

1

/

3

=

(

2

(

2

+

3

)

2

)

1

/

3

=

(

2

(

2

+

3

)

)

1

/

3

=

(

3

)

1

/

3

=

mn=((a+

a

2

+b

3

)(a−

a

2

+b

3

))

1/3

=(a

2

−(

a

2

+b

3

)

2

)

1/3

=(a

2

−(a

2

+b

3

))

1/3

=(−b

3

)

1/3

=−b

7. Substitute Values in the Expansion:

Recall the expansion

3

=

3

+

3

+

3

(

+

)

x

3

=m

3

+n

3

+3mn(m+n) :

Using

+

=

m+n=x ,

3

+

3

=

2

m

3

+n

3

=2a , and

=

mn=−b , it follows that:

3

=

2

+

3

(

)

x

3

=2a+3(−b)x

8. Result:

Rearrange the terms:

3

+

3

=

2

x

3

+3bx=2a

Thus, we have proved that:

3

+

3

=

2

x

3

+3bx=2a

as required.

Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.